Iterative spatial sectoring algorithm: a computer based approach to determining area of irregular closed space and tumor volume - Aboaba, Abdulfattah A.; Hameed, Shihab Ahmed; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Harun, Rahmat H.; Mohd Zain, Nurzaini Rose (Universiti Teknologi Petronas, 2011)
Measuring the properties of regular shapes like triangles, parallelogram, and geometric figures like circle, and spheres have well established methods and formulae. On the contrary, measuring the parameters of irregular shapes and particularly area of irregular closed space with snaky or wobbled edge is yet to have a definitive and assured approach, thus, measuring the parameters of such shape relies on approximation methods. The approximation made at the stage of finding the area would affect the determination of brain tumor volume and shape when it is eventually used in its calculation. The Iterative Spatial Sectoring algorithm presented in this paper is the stepwise approach of a novel idea leading to precise determination of area of irregular snaky edged close space. It is a promising technique based on preliminary manual test.